Conserving Nature Representation in Miyori no Mori Anime as a Teaching Media for Children’s Moral Education - Fauzy Wachyu Nur (EDP Sciences, 2021)
This paper discusses moral education in Miyori no Mori anime. Moral education exists in this anime as a teaching about the importance of conserving nature. Miyori no Mori is an anime about Miyori, an 11 years old girl who moved from Tōkyō into the Komori countryside. Miyori, as the chosen guardian by the yōkai forest spirit of the Komori’s forest, attempts to protect the countryside forest from a corporation that wants to build a dam inside the forest by destroying the whole forest area and jeopardizing the countryside. Representations of conserving nature in the anime can be observed through the conveyed moral values message explicitly and implicitly present in this anime. This paper aims to explain the conveyed messages of the Japanese moral education inside the anime for the importance of maintaining the core value belief by protecting the nature in between society to conserving nature. This paper methodology uses sociology of literature, the primary data object of this paper taken from the anime’s characters interaction, behaviours, and conflicts by descriptive analyzing then reinterpret, represent, and conclude the analysis of moral education importance for conserving nature. The results suggested that Japanese’s moral values and environmental ethics are represented.